Artistic and comparative manifestations of Dagestan in the Syrian novel(The novel The Story of My Grandfather by Olfa Al-Idlibi is an example) (Damascus University Journal of arts and humanities sciences, 2024)
The importance of the literature that produced the writer Olif Al-Idlibi lies in many aspects. However, this dependency was affected by the fact that the writer is one of the pioneers of narrative art in Syria, in addition to the abundance of production of comics and novels that she published, despite what some have launched of hasty downloading of this production. In that it is characterized by traditionalism, this does not degrade its status, especially if it is judged by the time in which it was produced. This, of course, applies to the production of literature in advanced stages. No one denies the development that is perfected in literary contribution and has appeared clearly in many interpretations.The importance of narrating the story of my grandfather lies in the fact that this creative experience was formulated by Al-Arauba in the guise of the story that she transmits from her mother, who used to tell it about her father. In this novel, the supposed realism and the sophisticated literary style are mixed on the one hand, and on the other hand we find a merging between the self of thenarrator, who belongs to the Levantine society, and that The close connection to the history of the deep roots of the family to which a large part belongs, and thus its artistic depiction of Dagestan - even if it is narrated and transmitted from another source - has become mixed, but rather the product of the connection with this country.In light of the presence of the current and strong affiliation to the Levant and Syria, this depiction leaned toward comparison in a large part of it, and all of this contributed to completing all aspects of the pictorial scene, especially when it combined in the ego what made it another relative, or perhaps vice versa, and this is what makes the recipient able to Capturing the features of the Dagestani identity that appeared in our Syrian novel, as well as monitoring the artistic and pictorial features through which this image was revealed.
Keywords: Artistic photography; Comparison; Dagestanm; The ego; The other